Realization of the process of forming of future social workers readiness to professional communication during doing different types of pedagogical practical work - Дмитренко, К. А.; Полякова, І. В. (Scientific notes of the pedagogical department, 2018)
The article state and analyses the theoretical basis of realization of the process of forming of future social workers readiness to professional communication during doing different types of pedagogical practical work. Different opinions of both native and foreign scientists, who were engaged in solving the problem of communicative skills formation and significance of pedagogical practical work in the process of forming of professional readiness of an employee, are presented. It has been proved that the main work regarding forming of students’ readiness to professional communication in the process of pedagogical practical work consists of conducting lectures, seminars, practical training during different subjects with the use of teaching methods based on games, active and interactive methods and working out recommendations for teachers, heads of pedagogical practical work from the social work and social pedagogy sub-faculty concerning realization of the process of forming of future social workers readiness to professional communication in the process of pedagogical practical work. The opinion is given that the main emphasis should be made on organization of professional oriented and individual work. Particularly, the introduction of such types of practical work, which help to solve the problem situations in the work with the subject of social interaction. According, to the authors, rather effective forms of work are the ones, which have been applied to extracurricular process such as press-center, drama studio “Forum-theatre”, association of volunteers and others. It was substantiated that the system of bases of practical work created by the authors allows to take into account individual wishes of student when choosing a specific institution as the base of practical work; to choose such institutions for every type of practical work where the conditions, the most necessary to perform the invariant and variant educational professional and communicative assignments of practical work program, have been created; to organize the practical work in small group or even individually that helps to improve the quality of supervision. It has been concluded that during the process of implementation of individual tasks and solution of problems in the process of doing different types of practical work, students should not only demonstrate all the knowledge, skills and abilities, which were formed when studying different academic disciplines, but also be able to combine them organically with the knowledge skills and abilities, which were formed during doing practical work of different types for effective professional communication, interaction and contact in the process of self-education and realization of analysis of communicative skills, techniques and others.